Effects of neuromuscular taping on muscular strength, range of motion and pain intensity in the glenohumeral joint in professional handball athletes: blinded randomized clinical trial - Lima, Cristiane Rissatto Jettar; Pires, Paulo Fernandes; Hartz, Charlini Simoni; Castro, Ester Moreira de; Pelai, Elisa Bizetti; Bigaton, Delaine Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Recent investigations in handball athletes point to the need to carry out rehabilitation programs that aim to improve the instability of the glenohumeral joint, widely used in the various tasks of this modality. Objectives: To evaluate the immediate and short‑term effects of a neurofunctional elastic bandage (NEB) on muscular strength, range of motion and pain intensity in the glenohumeral joint in handball athletes with shoulder dysfunction. Method: This study was composed of 20 professional male handball athletes who presented shoulder pain at rest and dysfunction of the shoulder, divided into two groups; experimental (n = 10) and placebo (n = 10). Before and one hour after the application of NEB the following were evaluated: maximal isometric muscular strength during movements of the glenohumeral joint (load cell), the range of motion (ROM) of the glenohumeral joint (fleximetry), pain intensity in the shoulder at rest and during movement, and the pressure pain threshold (algometry). NEB was maintained for 72 hours in all volunteers, during which a diary of shoulder pain was recorded for the short-term assessment. We used the ANOVA two-way repeated measures considering the possibility of group by time interaction, adopting a 5% level for significant differences. The treatment effect size was analyzed by means of Cohen’s d values. Results: There was no group by time interaction for any of the variables (p> 0.05), however, there was a large effect of the treatment for reducing pain in the experimental group after the application of NEB in the short-term period (d = 0.83). Conclusion: There were no significant effects on muscular strength, range of motion or pain intensity in the shoulder in handball athletes immediately after implementation of NEB.